Databook of green solvents - Wypych, Anna; Wypych, George (ChemTec Publishing, 2019)
Databook of Green Solvents, Second Edition, includes data and information that is divided into five separate sections: General, Physical, Health, Environmental and Use. Readers interested in this subject should note that two other volumes on all essential areas of solvent usage have also been published. They include Handbook of Solvents. Volume One, Properties and Handbook of Solvents, Volume Two: Use, Health, and Environment. Together, these books provide the most comprehensive information on the subject matter. The books are the authoritative sources of knowledge, with information updated from the most recent literature and developments occurring in the field of solvents.